Pelatihan Penggunaan Media Pembelajaran Digital Untuk Tutor Bimbingan Belajar Era 4.0 - Pixyoriza, Pixyoriza; Widyawati, Santi; Khoiriyah, Binti; Prestika, Aulfa Reyza Ayuni; Fajri, Cholida Nur (Jurnal SOLMA, 2025)
The development of information technology in the Industrial Revolution 4.0 era demands innovation in the world of education, including in the non-formal education sector such as tutoring. One innovation that can be applied is the use of interactive digital learning media such as Kahoot. This training activity aims to improve tutor competence in using Kahoot as an interesting and enjoyable evaluation and learning media for students. The training was attended by 15 tutors from various tutoring institutions and was carried out offline in the form of an integrated workshop. The training method includes an introduction to the Kahoot feature, quizzes, and simulations of application in the context of learning. The results of the training showed an increase in participants' understanding and skills in using Kahoot, marked by an increase in post-test scores and high enthusiasm during practice. Most tutors expressed their readiness to implement Kahoot in tutoring sessions. Although there were several obstacles such as limited internet access, this training proved effective in supporting the digital transformation of non-formal learning. Thus, similar training is recommended to be expanded as part of strengthening the capacity of teaching staff in the digital era..